Water management in Brussels: knowledge gained from the long time data series of the Flowbru regional telemetry system - Nicolas de Ville; Michel Verbanck (Brussels Studies, 2017)
The long time data series provided by the Flowbru regional hydrometric network (www.flowbru.be) represents a new opportunity to gain knowledge on the hydrographical system in Brussels. With a combination of data mining analysis, data consolidation, models and in-depth data interpretation, new insights on sewer system performance are obtained. First, the problem of the infiltration of parasitic clear water into the sewer system is addressed. A new methodology is developed to compute the daily volumes of clear water infiltrated in the entire zone treated by the Brussels-North Wastewater Treatment Plant (WWTP). We show the strong seasonal variation of infiltration and how this pattern can be identified in limnimetric time series to highlight sewers which are subject to infiltration. Secondly, the sewer sediment accumulation in the Brussels Right main collector – the largest sewer in the Brussels Region – is studied. The accumulation dynamics are discussed, and a comparison between the present situation and that of the 1980s shows the massive increase in sediment accumulation in recent decades. The potential causes and consequences of this accumulation are discussed briefly.